Historic Technical News Items - Moorhead, Simon (Journal of Telecommunications and the Digital Economy, 2019)
Two historic technical news items from 1970 covering the Australian Post Office’s involvement in the Apollo 13 emergency and a non-theoretical review of laser developments.